2012
DOI: 10.1016/j.ydbio.2011.10.015
|View full text |Cite
|
Sign up to set email alerts
|

BMP4 signaling directs primitive endoderm-derived XEN cells to an extraembryonic visceral endoderm identity

Abstract: The visceral endoderm (VE) is an epithelial tissue in the early postimplantation mouse embryo that encapsulates the pluripotent epiblast distally and the extraembryonic ectoderm proximally. In addition to facilitating nutrient exchange before the establishment of a circulation, the VE is critical for patterning the epiblast. Since VE is derived from the primitive endoderm (PrE) of the blastocyst, and PrE-derived eXtraembryonic ENdoderm (XEN) cells can be propagated in vitro, XEN cells should provide an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 99 publications
10
77
2
Order By: Relevance
“…S6). The expression of endoderm transcription factors is not upregulated compared with untreated controls, with the exception of Gata4, which is over twofold enriched, confirming previous observations (Artus et al, 2012). Taken together, this demonstrates that cXEN cells, like embryo-derived XEN cells, have the capacity to differentiate into VE cells in response to BMP4 treatment.…”
Section: Research Articlesupporting
confidence: 88%
See 1 more Smart Citation
“…S6). The expression of endoderm transcription factors is not upregulated compared with untreated controls, with the exception of Gata4, which is over twofold enriched, confirming previous observations (Artus et al, 2012). Taken together, this demonstrates that cXEN cells, like embryo-derived XEN cells, have the capacity to differentiate into VE cells in response to BMP4 treatment.…”
Section: Research Articlesupporting
confidence: 88%
“…Recently, a subtype of VE cells has been differentiated from embryo-derived XEN cells treated with BMP4, demonstrating the plasticity of XEN cells (Paca et al, 2012;Artus et al, 2012 Fig. S5).…”
Section: Cxen Cells Undergo Ve Differentiation In Response To Bmp Trementioning
confidence: 96%
“…Recent studies on mouse XEN cells demonstrated that Nodal/ Cripto signaling induced the anterior VE formation ( Kruithof-de Julio et al, 2011), whereas BMP4 promoted the extraembryonic VE differentiation (Artus et al, 2012;Paca et al, 2012). We found that treatment with Nodal did not cause any morphological transition in rat XEN cells (data not shown).…”
Section: Formation and Characterization Of Tight Junctions In The Presupporting
confidence: 52%
“…We found that treatment with Nodal did not cause any morphological transition in rat XEN cells (data not shown). However, when we treated the cells growing on laminin in N2B27 medium with BMP4 following the established protocol (Artus et al, 2012;Paca et al, 2012) (Fig. 5A), we noted the formation of an epithelium on day 2 (1 day after the BMP4 treatment) (Fig.…”
Section: Formation and Characterization Of Tight Junctions In The Prementioning
confidence: 97%
See 1 more Smart Citation